Recent progress of magnetorheological elastomers: a review - Bastola, Anil K; Paudel, Milan; Li, Lin; Li, Weihua (Smart materials and structures, 2020)
Magnetorheological elastomers (MREs) are one of the categories of smart materials, whose modulus increases considerably in the presence of a magnetic field. These elastomers are prepared by dispersing magnetic micro-sized particles into a soft solid carrier medium. The main feature of these elastomers is that they change their elastic and damping properties quickly in the presence of a magnetic field. The change in properties, also known as the magnetorheological (MR) effect of MREs are dependent on various parameters such as type of matrix material, distribution of magnetic particles, additives, working mode, and strength of the applied magnetic field. Various studies have been conducted to improve the MR effect and seek the possibility to implement the MREs in different applications including but not limited to vibration absorbers, isolators, soft actuators, and sensors. The focus of this review is to present the recent progress of MREs including materials used, fabrication strategies, MR effect, and potential applications.